PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. INDONESIA EPSON INDUSTRY - Jarot Ahmad Fadly; Nuridin (Jurnal Manajemen Bisnis Krisnadwipayana, 2021)
To determine the effect of competence and motivation on employee performance PT Indonesia Epson Industry. This research is included in the category of causal associative research using a quantitative approach. The research was conducted by distributing questionnaires to 30 respondents, all of whom were employees of PT Indonesia Epson Industry, while the research method used simultaneous and partially linear regression analysis. The hypothesis states that simultaneous competence and motivation have a positive effect on employee performance. The hypothesis which states that competence and motivation partially have an effect on employee performance and the coefficient of determination shows that competence and motivation contribute 69.2% to employee performance at PT Indonesia Epson Industry.